Robot-assisted laparoscopic combined with endoscopic partial gastrectomy (RALE-PG) for the treatment of gastric gastrointestinal stromal tumors in challenging anatomical locations: single-center experience - Jian, Chenxing; Huang, Xinxiang; Lin, Ruirong; Yang, Weijin; Zheng, Shiyao; He, Hongxin; Jin, Shangkun; Yang, Chunkang; Guan, Shen (Frontiers in Surgery, 2024)
Background: Gastric gastrointestinal stromal tumors in challenging anatomical locations are difficult to remove. Methods: This study retrospectively analyzed the clinical data of 12 patients with gastric GISTs in challenging anatomical locations who underwent robot-assisted laparoscopic combined with endoscopic partial gastrectomy (RALE-PG) and manual suturing of the gastric wall. Results: This study included 12 patients with a mean age of 56.8±9.8 years and a mean BMI of 23.9±1.9 kg/m2. Tumors were located in the GEJ (n=3), lesser curvature (n=3), posterior gastric wall (n=3) and antrum (n=3). The cardia and pylorus were successfully preserved in all patients regardless of the tumor location. The mean tumor size was 4.5±1.4 cm. The mitotic-count/50 mm2 was less than 5 in all patients (100%).There was no intraoperative tumor rupture (0%) and no conversion to open surgery (0%). The median operation time was 122 (97-240) min, and the median blood loss volume was 10 (5-30) ml. The median postoperative VAS score was 2 (2-4). The median time to first flatus was 2 (2-3) days. The median time to first fluid intake was 2 (2-3) days. The median time to first ambulation after the operation was 3 (2-4) days. No cases of anastomotic stenosis or leakage were found. The median time to drain removal for 6 patients was 5 (4-7) days. The median time to nasogastric tube removal for all patients was 2 (1-5) days. The median postoperative hospital stay was 5 (4-8) days.One patient (female/41 y) developed moderate anemia (Clavien-Dindo grade II complication). There was no unplanned readmission within 30 days after the operation. The median distance from the tumor to the resection margin was 1 (1-2) cm. R0 resection was achieved in all patients. The median follow-up period was 19 (10-25) months, and all patients survived with no recurrence or metastasis. Conclusions: RALE-PG is a safe, feasible and advantageous technique for treating GISTs in challenging anatomical locations. It can be used to accurately remove the tumor while preserving gastric function to the greatest extent, but long-term oncologic outcomes need to be evaluated in a study with a larger sample size and longer follow-up period.